Inovasi Pengelolaan Sampah untuk Kelestarian Lingkungan dan Pemberdayaan Ekonomi: Kasus Nagari Sulit Air - Alfisha Putri; Puteri Salsabila; Fadhila Surahmi; Fajar Rizki (Kajian Ekonomi dan Akuntansi Terapan, 2025)
Waste management is a serious challenge in many regions, including Nagari Sulit Air, which is experiencing an increase in waste volume due to population growth and economic activity. This study aims to explore innovations in waste management that are not only focused on environmental sustainability but also capable of empowering the local economy. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation studies of the waste management programs implemented in the nagari. The findings show that the community of Nagari Sulit Air has developed various innovative initiatives, such as waste banks, the processing of organic waste into compost, and creative recycling training for local residents, particularly women and youth. These innovations have proven effective in reducing waste volume and increasing environmental awareness among citizens. On the other hand, these activities also create new economic opportunities through the sale of recycled products and compost. This study highlights the importance of collaboration between the nagari government, the community, and third parties in establishing a sustainable and inclusive waste management system. The findings are expected to serve as a model for other regions in integrating environmental and economic aspects within community-based waste management practices.